2004
DOI: 10.1086/422997
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus (MRSA) Nares Colonization at Hospital Admission and Its Effect on Subsequent MRSA Infection

Abstract: MRSA colonization of nares, either present at admission to the hospital or acquired during hospitalization, increases the risk for MRSA infection. Identifying MRSA colonization at admission could target a high-risk population that may benefit from interventions to decrease the risk for subsequent MRSA infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
325
3
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(345 citation statements)
references
References 34 publications
10
325
3
5
Order By: Relevance
“…This rate is comparable with rates reported elsewhere. 1,29 Older age, intensive care unit stay, receipt of hemodialysis, presence of surgical wounds, presence of pressure ulcers, and use of intravascular catheters have been associated with an increased progression of MRSA colonization to invasive infection. 1,29 ' 30 In our study, a higher number of risk factors at the end of follow-up was associated with an increased risk of MRSA infection.…”
Section: Mrsa Infection During Follow-upmentioning
confidence: 99%
“…This rate is comparable with rates reported elsewhere. 1,29 Older age, intensive care unit stay, receipt of hemodialysis, presence of surgical wounds, presence of pressure ulcers, and use of intravascular catheters have been associated with an increased progression of MRSA colonization to invasive infection. 1,29 ' 30 In our study, a higher number of risk factors at the end of follow-up was associated with an increased risk of MRSA infection.…”
Section: Mrsa Infection During Follow-upmentioning
confidence: 99%
“…5,6 Previous studies 2,7,8 indicated that colonization with MRSA was a risk factor for subsequent infections such as bacteremia, pneumonia, and skin and soft tissue infections. However, in another study, 9 MRSA colonization was a poor predictor of LRTI and bloodstream infection (BSI) due to MRSA that required antimicrobial therapy.…”
mentioning
confidence: 99%
“…2,3 Nasal colonization with S. aureus predisposes to subsequent infection, particularly in surgical patients. [4][5][6] Infections caused by methicillin-resistant S. aureus (MRSA) have been associated with increased mortality and hospital costs, compared with methicillin-susceptible strains. [7][8][9] Unidentified MRSA carriers serve as a potential reservoir for transmission.…”
mentioning
confidence: 99%